A polêmica sobre os transgênicos: Monsanto vs. MST - Brunelli, Anna Flora [UNESP] (My University, 2011)
Based on a discursive perspective, in this paper we analyze some aspects of the dialogue between the discourse in favor of and the one against transgenics in Brazil, by showing the dialogic relations that each of them engages with other discourses. We noticed that the anti-transgenics discourse, which opposes openly the pro-transgenics trend, has been built upon both the scientific and the leftist political discourses, whereas the pro-transgenics discourse has been constructed upon the scientific discourse and covertly polemicizes with its other.

Neste trabalho, adotando uma perspectiva discursiva, analisamos alguns aspectos do diálogo que se trava, no Brasil, entre o discurso pró e o anti-transgênicos, procurando evidenciar as relações dialógicas que cada um deles estabelece com outros discursos. Assim, notamos que o discurso anti-transgênicos, que polemiza abertamente com o pró- transgênicos, se constrói a partir do discurso político de esquerda e do discurso científico. Já o discurso pró-transgênicos se constrói a partir do discurso científico e polemiza veladamente com o seu outro.
The polemic about transgenic: Monsanto vs. MST
Keywords: Polêmica; Transgênicos; Relações dialógicas; Polemic; Transgenic; Dialogic relations